2020
DOI: 10.1111/vde.12915
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of spray‐based heat‐treated lactobacilli in canine atopic dermatitis: a preliminary, open‐label, uncontrolled study

Abstract: Background – Canine atopic dermatitis (cAD) is a common inflammatory and pruritic skin disease, with various treatment options. The use of topical products containing natural ingredients has proven increasingly popular. Objective – To evaluate the effects of a spray solution containing heat‐killed Lactobacillus rhamnosus and L. reuteri, on the clinical signs and cutaneous microbiota of atopic dogs. Conclusions and clinical importance – There was a significant and rapid decrease in the clinical signs associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Canine atopic dermatitis (CAD) is an immunoinflammatory cutaneous disease that causes itching (pruritis), swollen spots, and elevated dark gray patches on the paws, neck, ear, mouth, tail, armpit, thighs, and other sites [1,2]. Several owners observed that dogs with CAD start rubbing against objects, scratching, and biting their feet [3]. The etiology of CAD is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Canine atopic dermatitis (CAD) is an immunoinflammatory cutaneous disease that causes itching (pruritis), swollen spots, and elevated dark gray patches on the paws, neck, ear, mouth, tail, armpit, thighs, and other sites [1,2]. Several owners observed that dogs with CAD start rubbing against objects, scratching, and biting their feet [3]. The etiology of CAD is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…At each assessment the owner's previous digital PVAS10 evaluation was prepopulated, as this has been recently demonstrated to lead to better agreement between owners' perceptions and changes in pruritus scores and is believed to improve scoring reliability and effectiveness [94]. While other studies regularly employ use of this scale [49,63,64,[95][96][97][98][99][100], to our knowledge none have shown the score from the previous assessment, and, more commonly, less reliable versions of visual analogue scales or numerical scales are employed [75,101]. Given that dogs representing mild pruritus (digital PVAS10 < 3.6) were enrolled, an appropriate outcome threshold is normal to very mild pruritus (digital PVAS10-N: <2) [76].…”
Section: Discussionmentioning
confidence: 99%
“…Comparatively, in cAD, TP corresponds to the treatment of flares, or "reactive therapy"; SP corresponds to the prevention of flares, or "proactive therapy"; and PP corresponds to strategies or interventions that are implemented to avoid the development of the disease altogether. However, while there is extensive research to develop and improve existing treatments [7,27,28,30,33,35,[39][40][41][42][43] and even to develop proactive strategies [21,44], cAD primary prevention is entirely neglected. Despite Marsella (2013) suggesting that skin barrier repair interventions could prove beneficial when initiated in early life in cAD's predisposed breeds [45], research on these strategies has not been pursued.…”
Section: What Is Prevention?mentioning
confidence: 99%